The Legacy of Sport Events for Emerging Nations - Knott, Brendon; Tinaz, Cem (Frontiers in Sports and Active Living, 2022)
Large-scale and mega sport events (SMEs), such as Olympic Games and FIFA World Cups, have been more frequently hosted in emerging nations. Bidding and hosting SMEs is considered an object of policy for many emerging nations, with SMEs viewed as key factors in local and national development strategies. This has largely been driven by the assumption that their legacy provides solutions to economic, social, cultural, or political challenges. A variety of legacies have predominated the literature over the past two decades, however it is proposed that there is a difference in the types of legacies anticipated or realised within emerging nations. This study therefore aimed to determine the types of legacies anticipated or realised by emerging nations as a result of hosting sport events, and to determine if these differ from those of established nations. A systematic literature review followed the PRISMA approach to identify and select peer-reviewed articles that focused on legacies from major and mega-events hosted in emerging nations. A set of 96 publications were analysed qualitatively to reveal the key legacy themes. The findings confirm legacy as a growing body of knowledge in emerging nations, aligned with increasing event hosting. The findings reveal insights on the extent of literature on this topic in emerging nations, including the major nations, events, authors and publications represented. The discussion outlines key legacy focus areas for these nations and proposes a conceptualisation of future legacy research focus areas. The paper is therefore unique in its focus on emerging nations and contributes to a more nuanced understanding of sport event legacy within these nations.